The International Women's Movement and Women's Political Representation, 1893–2003 - Paxton, Pamela; Hughes, Melanie M.; Green, Jennifer L. (American Sociological Review, 2006)
Women's political representation, once considered unacceptable by politicians and their publics, is now actively encouraged by powerful international actors. In this article, the authors ask how the growth and discourse of the international women's movement affected women's acquisition of political power over time. To answer this question, they use event history techniques to address women's political representation in more than 150 countries over 110 years (1893–2003). They consider multiple political outcomes: female suffrage, first female parliamentarian, and achievement of 10, 20, and 30 percent women in a country's national legislature. The findings show that increasing global pressure for the inclusion of women in international politics and the changing discourse of the international women's movement help to explain women's acquisition of these multiple political outcomes. Furthermore, by adding these concepts to traditional domestic models of women in politics, the authors demonstrate that country-level political, social structural, and cultural characteristics cause countries to act in conjunction with, or in opposition to, these global pressures. This is the first time that research on women in politics has considered such a comprehensive list of countries, time points, and outcomes.